Transformation of tobacco (nicotiana tabacum) with the oil palm cinnamyl alcohol dehydrogenase 1 (CAD1) gene - Yee, Mei Foong (2015)
Lignification in plants occurs via the lignin biosynthetic pathway that involves a series of enzymes; among these enzymes is the cinnamyl alcohol dehydrogenase (CAD). CAD catalyzes the conversion of hydroxycinnamaldehydes into monolignols. In oil palm, two copies of the CAD gene have been identified (EgCAD1 and EgCAD2) and their functions are largely undetermined. Studying gene function in oil palm is generally time-consuming and technically difficult. Hence, the study of the CAD1 gene from oil palm was performed via transformation of tobacco (Nicotiana tabacum) due to its relatively short life cycle and well-established transformation protocol. Tobacco leaf discs were used as target samples for Agrobacterium-mediated transformation of pMDC32-EgCAD1 which carries a T-DNA region consisting of the oil palm CAD1 gene. Phylogeny study of the EgCAD family was also performed to establish the relationship of EgCAD1 with other members of the CAD family across different plant orders. The oil palm CAD1 shares a common ancestor with their counterparts in the angiosperm and gymnosperm lineages. The CAD phylogeny showed that EgCAD1 was clustered together with the genes from rice, pinus and banana, and they share the same recent common ancestor. The oil palm CAD1 was successfully integrated into the tobacco genome where positive PCR data showed a genomic region comprising the EgCAD1 in the pMDC32-CAD1 construct was amplified in the transformed tobacco plants. Normal phenotype of the transformed plants was observed. This study confirmed the successful integration of the EgCAD1 into the genome of tobacco and the establishment of CAD family phylogeny. The findings serve as a basis for functional characterization of EgCAD1 in the future.